Pathophysiological role of 27-hydroxycholesterol in human diseases. (January 2022) - Kim, Dayea; Lee, Kwang Min; Lee, Chanhee; Jo, Yeon Suk; Muradillaevna, Muradillaeva Shakhnoza; Kim, Jae Ho; Yoon, Jong Hyuk; Song, Parkyong
Abstract: Oxysterols are oxygenated cholesterol derivatives and important regulators of cholesterol metabolism, lipid homeostasis, the immune system, and membrane fluidity regulation. Although the detailed mechanism of action of oxysterols remains unclear, activation of some nuclear receptors, such as liver X receptor α (LXRα) and RAR-related orphan receptors, have been believed to be critical for the regulation of various physiological processes in multiple tissues. 27-Hydroxycholesterol (27-OHC) is an endogenous oxysterol, which has an intermediate function in cholesterol catabolism to bile acid synthesis. According to previous studies, however, there are opposing opinions on whether 27-OHC activates human LXR. Recently, several studies have shown that 27-OHC can activate or inhibit the function of estrogen receptors ERα and ERβ in a tissue-specific manner, indicating that the understanding of 27-OHC-mediated biological output is very complicated. This review summarizes the pathophysiological relevance of 27-OHC in various tissues, with a special discussion on their functions in human diseases.